Profitabilitas Memoderasi Pengaruh Green Accounting Dan CSR Terhadap Pertumbuhan Laba - Sutiani Sutiani; Ahmad Farid Dedyansyah; Irma Indira (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aimed to examine the effect of green accounting and corporate social responsibility (CSR) on profit growth, with profitability as a moderating variable, in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employed a quantitative approach using multiple linear regression analysis and Moderated Regression Analysis (MRA). The sample consisted of 13 mining companies selected through purposive sampling, resulting in 65 observations. The study utilized secondary data obtained from corporate financial reports and was analyzed using IBM SPSS software. The results of the study show that green accounting has a positive and significant effect on profit growth. While CSR has a negative and significant effect on profit growth, profitability has been proven to have a significant effect on profit growth. In addition, profitability has a significant effect on moderating the relationship between green accounting and profit growth. However, profitability is not able to moderate the influence of CSR on profit growth. These findings indicate that in companies with high levels of profitability, the influence of green accounting and CSR on profit growth tends to weaken.